Emergence of extended-spectrum beta-lactamases-producing Escherichia coli in community-acquired urinary infections in Casablanca, Morocco - Bourjilat, Fatna; Bouchrif, Brahim; Dersi, Noureddine; Gros Claude, Jean David Perrier; Amarouch, Hamid; Timinouni, Mohammed (The Journal of Infection in Developing Countries, 2011)
Introduction: Extended-spectrum beta-lactamase- (ESBL)-producing Escherichia coli are an increasingly significant cause of community-acquired infection worldwide. The aim of this study was to assess the prevalence of ESBL-producing E. coli in a community, to analyze the relationship between strains studied, and to characterize the ESBL genes involved in this resistance. Methodology: ESBL production was detected by the double disk synergy test. Genes encoding ESBLs (blaTEM, blaCTM, blaSHV) were identified by PCR and DNA sequencing. Conjugation experiments were performed to check the transferability of antibiotic resistance genes. Strain inter-relationships were studied by pulsed field gel electrophoresis. Results: Seven ESBL-producing E. coli were identified among the 535 E. coli isolates. Most of them expressed a CTX-M enzyme (6/7) with a predominance of CTX-M-15 (6/6). Two strains possessed TEM in combination with CTX-M-15 or SHV-5. Plasmid content and gene transfer analysis showed that resistance genes were carried by high molecular weight conjugative plasmids. PFGE analysis showed that the strains were not clonal. Conclusions: ESBL-producing E. coli from urinary tract infections in Casablanca belong to different clones and carry mobile beta-lactamase genes. It is therefore essential to monitor the epidemiology of ESBLs in E. coli and related organisms locally to effectively combat resistance.